The national and subnational prevalence of cataract and cataract blindness in China: a systematic review and meta-analysis - Song, Peige (J Glob Health, 2018)
BACKGROUND: Cataract is the second leading cause of visual impairment and the first of blindness globally. However, for the most populous country, China, much remains to be understood about the scale of cataract and cataract blindness. We aimed to investigate the prevalence of cataract and cataract blindness in China at both the national and subnational levels, with projections till 2050. METHODS: In this systematic review and meta-analysis, China National Knowledge Infrastructure (CNKI), Wanfang, Chinese Biomedicine Literature Database (CBM-SinoMed), PubMed, Embase, and Medline were searched using a comprehensive search strategy to identify all relevant articles on the prevalence of cataract or cataract blindness in Chinese population published from January 1990 onwards. We fitted a multilevel mixed-effects meta-regression model to estimate the prevalence of cataract, and a random-effects meta-analysis model to pool the overall prevalence of cataract blindness. The United Nations Population Division (UNPD) data were used to estimate and project the number of people with cataract and cataract blindness from 1990 to 2050. According to different demographic and geographic features in the six geographic regions in China, the national numbers of people with cataract in the years 2000 and 2010 were distributed to each region. RESULTS: In males, the prevalence of any cataract (including post-surgical cases) ranged from 6.71% (95% CI = 5.06-8.83) in people aged 45-49 years to 73.01% (95% CI = 65.78-79.2) in elderly aged 85-89 years. In females, the prevalence of any cataract increased from 8.39% (95% CI = 6.36-10.98) in individuals aged 45-49 years to 77.51% (95% CI = 71.00-82.90) in those aged 85-89 years. For age-related cataract (ARC, including post-surgical cases), in males, the prevalence rates ranged from 3.23% (95% CI = 1.51-6.80) in adults aged 45-49 years to 65.78% (95% CI = 46.72-80.82) in those aged 85-89 years. The prevalence of ARC in females was 4.72% (95% CI = 2.22-9.76) in the 45-49 years age group and 74.03% (95% CI = 56.53-86.21) in the 85–89 years age group. The pooled prevalence rate of cataract blindness (including post-surgical cases) by best corrected visual acuity (BCVA)<0.05 among middle-aged and older Chinese was 2.30% (95% CI = 1.72-3.07), and those of cataract blindness by BCVA<0.10 and cataract blindness by presenting visual acuity (PVA)<0.10 were 2.56% (95% CI = 1.94-3.38) and 4.51% (95% CI = 3.53-5.75) respectively. In people aged 45-89 years, the number of any cataract cases was 50.75 million (95% CI = 42.17-60.37) in 1990 and 111.74 million (95% CI = 92.94-132.84) in 2015, and that of ARC rose from 35.77 million (95% CI = 19.81-59.55) in 1990 to 79.04 million (95% CI = 44.14-130.85) in 2015. By 2050, it is projected that the number of people (45-89 years of age) affected by any cataract will be 240.83 million (95% CI = 206.07-277.35), and that of those with ARC will be 187.26 million (95% CI = 113.17-281.23). During 2000 and 2010, South Central China consistently owed the most cases of any cataract, whereas Northwest China the least. CONCLUSIONS: The prevalence of cataract and cataract blindness in China was unmasked. In the coming decades, cataract and cataract blindness will continue to be a leading public-health issue in China due to the ageing population. Future work should be prioritized to the promotion of high-quality epidemiological studies on cataract.